Influência de estilos de vida associados a hábitos alimentares no consumo de pratos prontos: estudo comparativo entre São Paulo e Roma - Siekierski, Paulette (2012)
The pivotal question that this thesis attempts to answer is: how do lifestyles influence eating habits associated with consumption of ready meals. It is known that changes in lifestyle of the western world population have increased the demand for convenience in meal preparation. Consumers are working longer hours, spending more time in traffic and they want to maximize leisure time which has been increasingly limited. As a result, they demand products and services that facilitate and support their busy lives (Olsen, 2010). In response to this demand, the food industry has expanded its options for meals (Geeroms et al., 2008). In this context, the objectives of this research are to analyze the influence of socio-demographic variables in the choice of the ready food; study the importance of the factors as health, taste, convenience and tradition in the consumption of ready meals; and to compare consumption habits of ready meals related with lifestyles in São Paulo and Rome. The literature reviews lifestyle, multiculturalism, food habits and consumption of ready meals. In this process, the measurement scale developed and validated abroad deemed most promising for this study were adapted to the context. Electronic instruments have been set up to collect data which were accessible via a link sent by e-mail to residents of São Paulo and Rome. We obtained 200 valid questionnaires in São Paulo and 155 in Rome. According to the results, consumers in the two cities have different styles in relation to food. A study from Vanhonacker et al. (2010) indicates that older populations of southern Europe are traditional in terms of eating habits. Similarly, in this work, consumers from Rome are more concerned with tradition and health, compared to consumers from São Paulo. According to Askegaard and Madsen (1998), the Germanic cultures are more concerned about their health and in Italy, the sensory element matters the most. This study indicated that in São Paulo, there is a greater emphasis on convenience and flavor. The flavor dimension is supported by the anthropologist Da Matta (2001), in the observation that one of the most important Brazilian social mirrors is food, with what he calls "food code" which theoretically expresses the society. According to him, for Brazilians, "knowing how to eat is far more refined than the simple act of eating" (2001, p. 55). The city of São Paulo is proud to be a gastronomic hub of social activities and many of those activities take place in social gatherings that involve food. Therefore, the flavor dimension is easily explained. Simultaneously, the convenience dimension is supported by another feature of the city, the fact that it is a large urban center. Maluf (2001) indicates that the circumstances of contemporary life and the impact of advertising have changed the acquisition and consumption of food, highlighting the relevance of prepared foods in São Paulo. The limitation of this study is the criteria of the convenience sampling. It is believed that these results may be relevant both for the development of new products and for the positioning of products and brands active in these markets, or even to identify new market segments or understand different generations of consumers.